The early shortwave stations a broadcasting history through 1945 - Berg, Jerome S., 1943- (McFarland & Co., Inc., Publishers, 2013)
"This year-by-year account chronicles the birth and operation of the large international broadcasters, as well as the numerous smaller stations that were a great attraction to the DXers, or long-distance radio enthusiasts. With more than 100 illustrations and extensive notes, bibliography and index, the book is a valuable starting point for further study and research"--